Navigating Streets, Restaurants, and Algorithms: A Study of Young Immigrant Food Delivery Couriers in Montréal and Toronto - Baril, Émile; Vultur, Mircea (Labour / Le Travail, 2025)
Major Canadian cities have seen an overrepresentation of young and immigrant workers delivering meals in their food delivery industries. This type of labour is increasingly done via online digital platforms. The objective of this article is to use interviews to analyze the working conditions and experiences of food delivery workers in Toronto and Montréal, highlighting the elements of precariousness that characterize this type of work. The degree to which customers perform managerial functions through digital platforms is only one of the various forms and aspects of algorithmic control experienced by delivery workers. Through 30 semi-structured interviews with delivery riders, and notes collected through participatory observation, this article presents commonly experienced negative aspects of platform work among young and immigrant delivery drivers.